PROGRAM VIDEO INTERAKTIF: SOLUSI MENCAPAI KOMPETENSI MATA KULIAH PRAKTIS PROGRAM STUDI ILMU KOMUNIKASI DI PERGURUAN TINGGI JARAK JAUH (PTJJ) - Nila K Windrati; Irsanti W Asih (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2009)
As a distance education institution, Universitas Terbuka (UT) employs an independent learning system where the learning materials are delivered to the students through media, mostly in text materials. As a consequence of the learning system employed by UT, the students do not have any chance in practical activities. In some of the study programs in UT, the practical materials are delivered to the students through text materials. In conventional university, the practical course materials usually are delivered in the face-to-face mode through practical activities. From the practical materials the students are expected to have practical skills. However, because of the independent learning system employed by UT, it is difficult for UT to conduct face to face practical activities. This article discusses a way to handle the mentioned problem by developing audio-visual learning media in the form of interactive video program, especially, a case of Public Speaking Subject in the Communication Studies Program, the Faculty of Social and Political Sciences in UT. The article discusses about a subject contains materials about public speaking techniques. These practical materials, such as body language, speaking style, and the use of presentation tools, would be expected to be a solution in reaching the competence of practical courses when delivered to the students through audio-visual examples.